2022
DOI: 10.1177/14771535221117365
|View full text |Cite
|
Sign up to set email alerts
|

From luminance to brightness: A data-driven approach to support brightness assessments in open plan offices

Abstract: People can instantly distinguish a brighter from a darker environment, but it is still unknown how to estimate brightness from the luminance distribution in complex visual scenes. In this study, we performed a meta-analysis of three experiments in which participants assessed brightness in an open plan office environment. Experiment 1 varied the luminance distribution on the wall, Experiment 2 varied the desk illuminance and Experiment 3 varied the ceiling illumination. Correlating various measures derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…A pilot experiment by Sullivan et al 19 was also conducted, which indicated that less uniformly lit spaces were evaluated as brighter. A similar result was also found in Tiller et al, 22 whereas the data in de Vries et al 18 suggested the opposite. The contradictory results may be attributed to the lack of an unambiguous definition of uniformity in complex scenes.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…A pilot experiment by Sullivan et al 19 was also conducted, which indicated that less uniformly lit spaces were evaluated as brighter. A similar result was also found in Tiller et al, 22 whereas the data in de Vries et al 18 suggested the opposite. The contradictory results may be attributed to the lack of an unambiguous definition of uniformity in complex scenes.…”
Section: Introductionsupporting
confidence: 80%
“…9 Other studies discovered that the average luminance and the standard deviation of the luminance distribution in the horizontal 40° band are good predictors for the acceptability of lighting scenes. 16,17 In a recent paper by de Vries et al , 18 a meta-analysis of three experiments assessing brightness in an open office environment was conducted. In the brightness-responsive group of observers, brightness was best modelled with the logarithm of the median luminance of a 60° horizontal band or the logarithm of the 95th percentile luminance over the median luminance in a 40° horizontal band.…”
Section: Introductionmentioning
confidence: 99%